Effects on proliferating hemangioma of corticosteroids and propranolol. - Colonna, V.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Oral corticosteroids were for decades the first choice drug in the treatment of severe hemangioma. In 2008 the efficacy of propranolol was unveiled. Today the latter is a valid alternative in the treatment of hemangioma. The mechanisms explaining their activity on proliferating hemangioma are not superimposable. These mechanisms were analyzed in the present study.